The search algorithm for optimal reliability increasing system parameters in 10 kv branched distribution networks - Тимчук, Сергей Александрович; Сиротенко, Михаил Александрович (Eastern-European Journal of Enterprise Technologies, 2015)
To increase the reliability of power supply to consumers in 10 kV distribution networks, various devices are used, such as pointers of damaged areas, line isolators, automatic partitioning devices and automatic transfer switches. Optimization of the arrangement of reliability increasing means is an urgent task. However, existing computational methods either do not consider the possibility of installing several types of devices in the network at once, or require performing a large number of iterations when searching for the optimal layout. To solve this problem, it is proposed to apply an algorithm that uses the features of the object of research, namely the property of optimal layout of RIM in the distribution network with the priority of one of the criteria for i points occupied by devices, always include the optimal layout of RIM with the priority of the same criterion for (i-1) points. Using the proposed algorithm allowed to carry out the computational study of the impact of PTL parameters on the structure of the optimal reliability increasing system and the effect of its installation. The experiment showed that the arrangement of RIM will significantly reduce the expected damage from annual undersupply of electric power, as well as the average time to search for the damaged area in both redundant and non-redundant branched distribution networks. The importance of the results lies in the fact that the efficiency of installation of the line isolator together with the pointer of the damaged area that has the ability to transmit information on the damaged area to the control point, compared to other RIM installed in 10 kV non-redundant networks was first shown.